GROWTH AND YIELD OF RICE (Oriza sativa L) DUE TO WATER EFFICIENCY AND FERTILIZER COMPOSITION - Driska Arnanto; Sri Widata; Darnawi Darnawi; Novita Dwi Anggraeni (AGRORADIX : Jurnal Ilmu Pertanian, 2023)
This study aims to determine the effect of the volume of water application and the composition of goat manure and urea on the growth and yield of sunggal rice varieties. This research was conducted in Kepuhan Hamlet, Argorejo Village, Sedayu District, Bantul Regency, DIY from September to December 2021. The experimental design in this study was a Completely Randomized Design (CRD) with 3 replications. There are two factors consisting of the volume of water supply, namely: N1 (300 ml), N2 (600 ml), N3 (900) and the composition factor of goat manure: urea, namely: P1 {80% (31.4 g):20 % (7.85 g)}, P2 {50% (19.625 g):50% (19.625 g)} and P3 {20% (7.85 g):80%(31.4 g)}. There were two variables observed, namely growth variables including plant height, number of tillers, fresh weight of stover, and dry weight of stover and yield variables including number of panicles, panicle length, percentage of grain content, weight per 1000 grains, weight of grain per clump and weight of grain. contents per clump. Observational analysis used variance at a level of 5%, followed by Duncan's Multiple Range Test (DMRT) at a level of = 5%. The results showed that the volume of water treatment and the composition of goat manure showed no interaction with all growth variables, but there was a significant difference in the fresh weight of the stover. Meanwhile, for the treatment variable, the volume of N1 water as much as 300 ml and the composition of goat manure and urea P2 50%:50% showed an interaction with the yield variable, namely weight of grain per clump and weight of filled grain per clump.